von Bertalanffy growth model with autocorrelated errors - Venugopalan, R; ., Prajneshu (Indian Journal of Fisheries, 2011)
Three procedures namely, linearised version of the von Bertalanffy growth (VBG) model, nonlinear estimation of the VBG model with independently and identically distributed (i.i.d) error term, and nonlinear estimation of the VBG model with autocorrelated errors were applied to the age-length data of Indian mackerel under the assumptions of monophasic as well as diphasic growth. Based on sound statistical techniques, it is demonstrated that nonlinear estimation procedure with autocorrelated error structure performs the best.